Assessment of the Effectiveness of Ich Tam Khang as a Supportive Therapy for Chronic Heart Failure - Vu, Bien D.; Pham, Son N.; Le, Thanh D.; Nguyen, Ly K.; Luong, Dang H.; Luu, Quynh; Dang, Duc V.; Hoang, Ba X. (Journal of Nutritional Therapeutics, 2014)
Background: Heart failure is a chronic disease needing lifelong management. Despite the advances that have been made in the treatment of the disease, both the longevity and quality of life for those with chronic heart failure remain impaired. A more effective therapeutic approach with less negative side effects is still needed. In this study, we evaluate Ich Tam Khang (ITK), the poly-ingredient herbal and nutritional preparation with multiple physiological actions, as a supportive therapy for patients with chronic heart failure. Aims of Study: To evaluate the effectiveness and safety of Ich Tam Khang as an adjunctive treatment of chronic heart failure. Methods: A total of 60 patients with chronic congestive heart failure were enrolled in this open label, cross-sectional and prospective study. All patients were treated with a conventional regimen (digoxin, diuretics, angiotensin-converting-enzyme (ACE) inhibitors or angiotensin II receptor blockers (ARBs), beta blockers) for at least 4 weeks before being divided into two equal groups. In the treated patients with ITK, patients received conventional therapy plus 4 tablets ITK per day added in two divided doses. In the control patients, all patients kept the same conventional regimen without ITK. All patients were followed up for 3 months for clinical and para-clinical outcomes. Result: The symptoms of heart failure (dyspnea, palpitation, peripheral edema, neck vein distention, heptojugular reflex) decreased. Heart rate and blood pressure stabilized during treatment in the treated patients with ITK. Additionally, total cholesterol and HDL-cholesterol normalized in the patients treated with ITK. Most of echocardiography parameters in the ITK treated patients were superior to the control patients. ITK is safe and it has no side effects. Conclusion: ITK as a combination of herbal and nutritional preparation is effective in reducing heart failure symptoms, improving patient’s quality of life for the patients with decompensated heart failure and reducing total cholesterol and LDL-C.